Global study of anti-NMDA encephalitis: a bibliometric analysis from 2005 to 2023 - Song, Xinyue; Luo, Zixin; Huang, Duoqin; Lv, Jialian; Xiao, Li; Liang, Ting; Zou, Kang (Frontiers in Neurology, 2024)
Background: Autoimmune diseases have always been one of the difficult diseases of clinical concern. Because of the diversity and complexity of its causative factors, unclear occurrence and development process and difficult treatment, it has become a key disease for researchers to study. And the disease explored in this paper, anti-NMDA encephalitis, belongs to a common type of autoimmune encephalitis. However, the quality of articles and research hotspots in this field are not yet known. Therefore, in this field, we completed a bibliometric and visualization analysis from 2005 to 2023 in order to understand the research hotspots and directions of development in this field.We searched the SCI-expanded databases using Web of Science's core databases on January 22, 2024 and used tools such as VOS viewer, Cite Space, and R software to visualize and analyze the authors, countries, journals, institutions, and keywords of the articles.Results: A total of 1161 literatures were retrieved and analyzed in this study. China was the country with the most total publications, and USA and Spain were the most influential countries in the field of anti-NMDA encephalitis. University of Pennsylvania from USA was the institution with the highest number of publications.While Dalmau Josep is the most prolific, influential and contributing author who published one of the most cited articles in Lancet Neurology, which laid the foundation for anti-NMDA encephalitis research, the top three appearances of keyword analysis were: "antibodies ", "diagnosis" and "autoimmune encephalitis".Bibliometric analysis shows that the number of studies on anti-NMDA encephalitis is generally increasing year by year, and it is a hot disease pursued by researchers. USA and Spain are leading in the field of anti-NMDA encephalitis, while China should continue to improve the quality of its own research. The suspected causes of anti-NMDA encephalitis other than ovarian teratoma and herpes simplex, the specific clinical manifestations that are not masked by psychiatric symptoms, the diagnostic modalities that are faster and more accurate than antibody tests, and the improvement of treatment modalities by evaluating prognosis of various types of patients are the hotspots for future research.